Glycyrrhiza uralensis polysaccharides ameliorates cecal ligation and puncture-induced sepsis by inhibiting the cGAS-STING signaling pathway - Hui, Siwen; Kan, Wen; Qin, Shuanglin; He, Ping; Zhao, Jia; Li, Hui; Bai, Jun; Wen, Jincai; Mou, Wenqing; Hou, Manting; Wei, Ziying; Lin, Li; et al. (Frontiers in Pharmacology, 2024)
Ethnopharmacological relevance:G. uralensis Fisch. (Glycyrrhiza uralensis) is an ancient and widely used traditional Chinese medicine with good efficacy in clearing heat and detoxifying action. Studies suggest that Glycyrrhiza Uralensis Polysaccharides (GUP), one of the major components of G. uralensis, has anti-inflammatory, anti-cancer and hepatoprotective effects., but its exact molecular mechanism has not been explored in depth. Aim of the study: Objectives of our research are about exploring the anti-inflammatory role of GUP and the mechanisms of its action. Materials and methods: ELISA kits, Western blotting, immunofluorescence, quantitative real-time PCR, immunoprecipitation and DMXAA-mediated STING activation mice models were performed to investigate the role of GUP on the cGAS-STING pathway. To determine the anti-inflammatory effects of GUP, cecal ligation and puncture (CLP) sepsis models were employed. Results: GUP could effectively inhibit the activation of the cGAS-STING signaling pathway accompany by a decrease the expression of type I interferon-related genes and inflammatory factors in BMDMs, THP-1, and human PBMCs. Mechanistically, GUP does not affect the oligomerization of STING, but affects the interaction of STING with TBK1 and TBK1 with IRF3. Significantly, GUP had great therapeutic effects on DMXAA-induced agonist experiments in vivo as well as CLP sepsis in mice. Conclusion: Our studies suggest that GUP is an effective inhibitor of the cGAS-STING pathway, which may be a potential medicine for the treatment of inflammatory diseases mediated by the cGAS-STING pathway.